AFPM Machines Equipped With Multilayer Magnets - Darmani, Mostafa Ahmadi; Poskovic, Emir; Franchini, Fausto; Ferraris, Luca; Cavagnino, Andrea; Gerada, Chris (IEEE transactions on energy conversion, 2025)
This article investigates the manufacturability and applicability of unified multilayer magnets, comprising two different magnetic materials with distinct characteristics, for use in electrical machines. In particular, the self-produced multilayer magnets are made of compressed NdFeB bonded powders for the ' strong ' magnet layer and hybrid composite materials for the ' weak ' magnet layer. Various combinations of material for the self-produced permanent magnets are experimentally investigated. Also, the suitability of resultant multilayer bonded magnets to electrical machines is articulated on the basis of finite element simulations. To assess their performance, three axial-flux surface-mounted permanent magnet machines are constructed: one conventional machine with single-layer bonded magnets as the reference, and two machines equipped with multilayer magnets with series and parallel configurations. The performance of the machines are evaluated in terms of the back-EMF, output torque, torque ripple, losses, efficiency, and cost. The findings indicate an appreciable enhancement in flux-weakening operation for the machine equipped with multilayer magnets, but at the expense of lower flux linkage values and nominal torque. Further analyses of the multilayer magnet's trade-offs and potential applications in electrical machines are presented.